Sport injuries treated at a physiotherapy center specialized in sports - Guilherme S. Nunes; Alessandro Haupenthal; Manuela Karloh; Valentine Zimermann Vargas; Daniela Pacheco dos Santos Haupenthal; Bruna Wageck
Abstract Introduction: The risk of injuries related to physical activity and sports may increase if there is predisposition, inappropriate training and/or coach guidance, and absence of sports medicine follow-up. Objective: To assess the frequency of injuries in athletes treated at a physiotherapy center specialized in sports. Methods: For the data collection was carried out the survey of injuries in records of athletes treated in eight years of activities. The data collected included: characteristics of patients, sport, injury kind, injury characteristics and affected body part. Results: From 1090 patient/athlete records, the average age was 25 years old, the athletes were spread across 44 different sports modalities, being the great majority men (75%). The most common type of injury was joint injury, followed by muscular and bone injuries. Chronic injury was the most frequent (47%), while the most common body part injured was the knee, followed by ankle and shoulder. Among all the sports, soccer, futsal, and track and field presented the highest number of injured athletes, respectively. Conclusion: Soccer was the most common sport among the injured athletes, injury kind most frequent was joint injuries and knee was the body part most injured. Chronic injuries were the most common.